Case report: atypical Silver-Russell syndrome patient with hand dystonia: the valuable support of the consensus statement to the wide syndromic spectrum - Vimercati, Alessandro; Tannorella, Pierpaola; Orlandini, Eleonora; Calzari, Luciano; Moro, Mirella; Guzzetti, Sara; Selicorni, Angelo; Crippa, Milena; Larizza, Lidia; Bonati, Maria Teresa; Russo, Silvia (Frontiers in Genetics, 2023)
The amount of IGF2 (Insulin Growth Factor 2) controls the rate of embryonal and postnatal growth. The IGF2 and adjacent H19 are the imprinted genes of the telomeric cluster in the 11p15 chromosomal region regulated by differentially methylated regions (DMRs) or imprinting centers (IC): H19/IGF2:IG-DMR (IC1). Dysregulation due to IC1 Loss of Methylation or Gain of Methylation causes Silver-Russell (SRS) or Beckwith-Wiedemann syndrome (BWS), disorders respectively associated with growth retardation or overgrowth. Specific features define each of the two syndromes, but isolated asymmetry is a common cardinal feature, considered sufficient for a diagnosis in the BWS spectrum. Here we report the case of a girl with right body asymmetry, which suggested BWS spectrum. Later, BWS/SRS molecular analysis identified an IC1_LoM revealing the discrepant diagnosis of SRS. A clinical re-evaluation identified a relative macrocephaly and previously-unidentified growth rate at lower limits of normal at birth, feeding difficulties and asymmetry. Interestingly, and never previously described in IC1_LoM SRS patients, since the age of 16 she has developed hand-writer’s cramps, depression, and bipolar disorder. Trio-WES identified a VPS16 heterozygous variant [NM_022575.4:c.2185C>G:p.Leu729Val] inherited from her healthy mother. VPS16 is involved in the endolysosomal system and its dysregulation is linked to autosomal dominant dystonia with incomplete penetrance and variable expressivity. IGF2 involvement in the lysosomal pathway led us to speculate that the neurological phenotype of the proband might be triggered by the concurrent IGF2 deficit and VPS16 alteration.